Fecundity performance of nilem (Osteochilus vittatus) from Cianjur, Tasikmalaya and Kuningan Districts, West Java, Indonesia - ROSTIKA, RITA; ANDRIANI, YULI; JUNIANTO, JUNIANTO (Asian Journal of Agriculture, 2017)
Rostika R, Andriani Y, Junianto. 2017. Fecundity performance of nilem (Osteochilus vittatus) from Cianjur, Tasikmalaya and Kuningan Districts, West Java, Indonesia. Asian J Agric 1: 17-21. The aim of this study was to know the reproduction aspects of nilem (Osteochilus vittatus Valenciennes, 1842; syn. Osteochilus hasseltii Valenciennes, 1842). The study was conducted from October 2015 to March 2016 that includes elements of body length, weight, gonad maturity level (GML) and fecundity. There were 27 samples collected from farming activities in Cianjur, Tasikmalaya and Kuningan West Java, Indonesia. The parameters observed were the correlation between weight and fecundity, correlation between body length and fecundity and GML. The method used was explorative approach and the data were analyzed by descriptive approach. The results showed that the correlation between weight and fecundity in Cianjur District was y= e0,024x, while the body length and fecundity was y=e0,413x. In Tasikmalaya District was y= e0,0728x, while the body length and fecundity was y=e0,4903x. In Kuningan District was y= e0,2902x, while the correlation between the length of the fish and fecundity was y=e0,6859x. The dominant gonad maturity level of Nilem in Cianjur was GML IV (50%), Tasikmalaya was GMLVI (100%), and Kuningan was GML V (55,56%) respectively. The relationship between length and body weight of Osteochillus vittatus from Cianjur, Tasikmalaya and Kuningan District were W=0,03L2,95, W = 0.04L2.89 and W = 0.04L2.79 respectively. The implication of this research is to know the proper size of nilem fish that can be harvested in conditions of optimum egg volume.